ANALYSIS OF PAYMENT SYSTEMS USING SHOPEE PAY-LATER REVIEWED FROM ISLAMIC ECONOMICS - Aryuandri, Indrika; Bustami, Alek Wissalam (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2024)
Based on Islamic Economics studies, research was conducted to analyse the Shopee Pay-Later payment system. This research is a content analysis. The research results show that the ShopeePayLater payment details include the due date. Regarding the absence of interest at the start of implementing this shopeepaylater feature, delaying financing to the following month or buying now, pay later financing, it even mentions 0% interest. Shopee Paylater credit practices are permissible (mubah) and haram permissible (mubah) because the contract is implemented, proven by the contract agreement between the seller and the buyer at the time of carrying out the hijab and Kabul as well as the additional price on Shopee Paylater. Credit practice is considered a deferred price and prohibited because the extra price in the Shopee Pay Later credit practice is riba, and usury is prohibited in Islamic business ethics. In contrast, the Shopee Paylater credit practice applies an additional price of 2.95% for paying off bills within two, three, and six months.